2015
DOI: 10.1097/brs.0000000000000845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Therapeutic Hypothermia on Apoptosis and Autophagy After Spinal Cord Injury in Rats

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Accumulating evidence has demonstrated that autophagy activation is elevated in the central nervous system under stressed conditions (Park et al, 2015;Li et al, 2015a;Villamil-Ortiz and Cardona-Gomez, 2015;Yang et al, 2015). As shown in the previous studies, autophagy plays an important role in spinal cord injury (Baba et al, 2009;Seo et al, 2015;Fujita et al, 2015); however, its expression change and mechanism after spinal cord I/R injury are largely unknown. Furthermore, the role of autophagy in ischemic injury remains controversial.…”
Section: Introductionmentioning
confidence: 85%
“…Accumulating evidence has demonstrated that autophagy activation is elevated in the central nervous system under stressed conditions (Park et al, 2015;Li et al, 2015a;Villamil-Ortiz and Cardona-Gomez, 2015;Yang et al, 2015). As shown in the previous studies, autophagy plays an important role in spinal cord injury (Baba et al, 2009;Seo et al, 2015;Fujita et al, 2015); however, its expression change and mechanism after spinal cord I/R injury are largely unknown. Furthermore, the role of autophagy in ischemic injury remains controversial.…”
Section: Introductionmentioning
confidence: 85%
“…Although adequate surgical decompression is the preferred treatment for SCI and results in favorable outcomes, SCI patients experience unpredictable and disastrous postoperative complications [25,26]. A series of studies have indicated that SERCA2 has significant protective effects on the heart, liver, and other tissues by reducing endoplasmic reticulum stress and apoptosis [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the protective effect of hormones on spinal cord neurons may occur through inhibition of autophagy in spinal cord neurons, thereby reducing autophagic cell death. Seo et al suggested that the treatment of spinal cord injury using a high dose of hormone could reduce the level of autophagy and apoptosis in injured spinal cord neurons to reduce spinal cord injury [26].…”
Section: Discussionmentioning
confidence: 99%